Treatments for COVID-19: emerging drugs against the coronavirus - Potì, Francesco; Pozzoli, Cristina; Adami, Maristella; Poli, Enzo; Costa, Lucio G. (Acta Biomedica Atenei Parmensis, 2020)
The Coronavirus disease 19 (COVID-19) outbreak has been recognized as a global threat to public health. It is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and no effective therapies currently exist against this novel viral agent. Along with extensive public health measures, an unprecedented global effort in identifying effective drugs for the treatment is being implemented. Potential drug targets are emerging as the result of a fast-evolving understanding of SARS-CoV-2 virology, host response to the infection, and clinical course of the disease. This brief review focuses on the latest and most promising pharmacological treatments against COVID-19 currently under investigation and discuss their potential use based on either documented efficacy in similar viral infections, or their activity against inflammatory syndromes. Ongoing clinical trials are also emphasized.